2022
DOI: 10.22541/au.164580004.43494403/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental RNA degrades more rapidly than environmental DNA across a broad range of pH conditions

Abstract: Although the use and development of molecular biomonitoring tools based on eNAs (environmental nucleic acids; eDNA and eRNA) have gained broad interest for the quantification of biodiversity in natural ecosystems, studies investigating the impact of site-specific physicochemical parameters on eNA-based detection methods (particularly eRNA) remain scarce. Here, we used a controlled laboratory microcosm experiment to comparatively assess the environmental degradation of eDNA and eRNA across an acid-base gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…An inverse-urnshaped pattern of the impact of pH on DNA degradation was noted for 24, 48, and 72 hours respectively. The obtained results were found to be in line with the other previously reported literature studies (Kagzi et al, 2022).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…An inverse-urnshaped pattern of the impact of pH on DNA degradation was noted for 24, 48, and 72 hours respectively. The obtained results were found to be in line with the other previously reported literature studies (Kagzi et al, 2022).…”
Section: Resultssupporting
confidence: 93%
“…Intrinsic variables include, among other things, body mass and surface area, but also age, sex, ante mortem medical problems, the presence of injuries/trauma, the amount of bacterial activity, and the cause of death. A thorough understanding of the susceptibility of post-mortem changes to such factors is critical because these are likely to affect both the appearance of the changes as well as the rate of decay, thus either speeding up or slowing down the progression of post-mortem events (Hau et al, 2014;Kagzi et al, 2022). This is undoubtedly one of the most important reasons why estimating the PMI has remained a difficult problem in forensic science for hundreds of years.…”
Section: Introductionmentioning
confidence: 99%
“…Most RNA molecules are only transcribed, and therefore present, in certain cell types and at certain times, so they may carry functional information about the physiological conditions of the host organism (Veilleux et al, 2021). As RNA is less stable than DNA, eRNA degrades more rapidly than eDNA does and so persists for a shorter time in the environment (Kagzi et al, 2022). For example, a study showed that eRNA in water from two marine invertebrates became undetectable after 13 h, compared to 94 h for eDNA from the same samples (Wood et al, 2020).…”
Section: New Frontiers In Fish Edna Researchmentioning
confidence: 99%
“…False discovery rate is defined as the number of false positives as a proportion of the sum of true positives and false positives. Some studies have proposed that eRNA might detect cellularly active taxa only, as opposed to dead and dormant taxa or resuspended sedimentary DNA, and thus minimize the false discovery rate when compared with eDNA (Dowle et al, 2015; Pawlowski et al, 2014; Pochon et al, 2017; Visco et al, 2015, although see Brandt et al, 2020); to date laboratory degradation experiments have found mixed results on whether eRNA degrades faster than eDNA (Kagzi et al, 2022; Wood et al, 2020). Further studies in a field setting will be needed to determine the advantages of eRNA of overcoming false positives detected by eDNA sampling, should they exist.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the false discovery rate between eDNA and eRNA. False discovery rate is defined as the num- Pochon et al, 2017;Visco et al, 2015, although see Brandt et al, 2020); to date laboratory degradation experiments have found mixed results on whether eRNA degrades faster than eDNA (Kagzi et al, 2022;Wood et al, 2020). Further studies in a field setting will be needed to determine the advantages of eRNA of overcoming false positives detected by eDNA sampling, should they exist.…”
Section: Discussionmentioning
confidence: 99%